Wishes for Christmas - Michaels, Fern (Michaels, Fern. Godmothers., 2015)
With the holidays approaching Sisterhood member Maggie Spitzer wants to bring joy to a teacher from her past, while Toots and the Godmothers investigate a mystery surrounding a designer at an exclusive Charleston firm.